Quantitative identification and segmentation repeatability of thoracic spinal muscle morphology. Issue 3 (1st July 2020) - Pai S, Anoosha; Zhang, Honglin; Shewchuk, Jason R.; Al Omran, Bedoor; Street, John; Wilson, David; Doroudi, Majid; Brown, Stephen H. M.; Oxland, Thomas R.
Abstract: Objective: MRI derived spinal‐muscle morphology measurements have potential diagnostic, prognostic, and therapeutic applications in spinal health. Muscle morphology in the thoracic spine is an important determinant of kyphosis severity in older adults. However, the literature on quantification of spinal muscles to date has been limited to cervical and lumbar regions. Hence, we aim to propose a method to quantitatively identify regions of interest of thoracic spinal muscle in axial MR images and investigate the repeatability of their measurements. Methods: Middle (T4‐T5) and lower (T8‐T9) thoracic levels of six healthy volunteers (age 26 ± 6 years) were imaged in an upright open scanner (0.5T MROpen, Paramed, Genoa, Italy). A descriptive methodology for defining the regions of interest of trapezius, erector spinae, and transversospinalis in axial MR images was developed. The guidelines for segmentation are laid out based on the points of origin and insertion, probable size, shape, and the position of the muscle groups relative to other recognizable anatomical landmarks as seen from typical axial MR images. 2D parameters such as muscle cross‐sectional area (CSA) and muscle position (radius and angle) with respect to the vertebral body centroid were computed and 3D muscle geometries were generated. Intra and inter‐rater segmentation repeatability was assessed with intraclass correlation coefficient (ICC (3, 1)) for 2D parameters and with dice coefficient (DC) for 3D parameters. Results: Intra and inter‐rater repeatability for 2D and 3D parameters for all muscles was generally good/excellent (average ICC (3, 1) = 0.9 with ranges of 0.56‐0.98; average DC = 0.92 with ranges from 0.85‐0.95). Conclusion: The guidelines proposed are important for reliable MRI‐based measurements and allow meaningful comparisons of muscle morphometry in the thoracic spine across different studies globally. Good segmentation repeatability suggests we can further investigate the effect of posture and spinal curvature on muscle morphology in the thoracic spine. Abstract : The quantitative morphology of thoracic spine muscles is important for biomechanical modeling, particularly in spinal deformity. This study presentation novel guidelines for the segmentation of key thoracic spine muscles from MRI.